2013
DOI: 10.1007/s11999-013-3231-0
|View full text |Cite
|
Sign up to set email alerts
|

Does the Direct Anterior Approach in THA Offer Faster Rehabilitation and Comparable Safety to the Posterior Approach?

Abstract: Background Newer surgical approaches to THA, such as the direct anterior approach, may influence a patient's time to recovery, but it is important to make sure that these approaches do not compromise reconstructive safety or accuracy. Questions/purposes We compared the direct anterior approach and conventional posterior approach in terms of (1) recovery of hip function after primary THA, (2) general health outcomes, (3) operative time and surgical complications, and (4) accuracy of component placement. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
162
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 34 publications
2
162
0
6
Order By: Relevance
“…The direct anterior approach to THA has been gaining popularity as a result of the proposed minimally invasive nature of this approach, faster and earlier recovery [1,8,22], and the reported lower incidence of dislocation after this technique [14,25]. Our study shows improvement in the variability of acetabular cup position after use of direct anterior approach THAs with fluoroscopy by a surgeon experienced in posterior approach THAs, however, there is a learning curve associated with the use of fluoroscopy to achieve improved accuracy in acetabular component positioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct anterior approach to THA has been gaining popularity as a result of the proposed minimally invasive nature of this approach, faster and earlier recovery [1,8,22], and the reported lower incidence of dislocation after this technique [14,25]. Our study shows improvement in the variability of acetabular cup position after use of direct anterior approach THAs with fluoroscopy by a surgeon experienced in posterior approach THAs, however, there is a learning curve associated with the use of fluoroscopy to achieve improved accuracy in acetabular component positioning.…”
Section: Discussionmentioning
confidence: 99%
“…There is some clinical data to support that it offers early recovery as compared with the lateral, anterolateral, and posterior approaches with no longterm clinical differences [1,8,21,22]. However, it has been shown to have a significant learning curve [3,26].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of groin pain remains a real one. Although our study did not demonstrate a statistical difference, it may have been underpowered to do so [7]. Focus on assuring anterior coverage of the implant by bone has diminished the issue at our center.…”
mentioning
confidence: 63%
“…Our recently published level 2 study comparing DAA with the posterior approach demonstrated objective and consistent benefits in early mobility, but most findings were equalized by 2 weeks post op, and by 6 weeks post op there was no measurable differences between the groups [7]. In addition, we have presented data on early recovery of muscle strength, showing DAA patients may have early flexion weakness, and posterior approach patients may have external rotation weakness, most of which resolves by 6 months [9].…”
mentioning
confidence: 73%
See 1 more Smart Citation